Changes in maximal cardiorespiratory capacity among aging municipal employees. - Ilmarinen, Juhani; Louhevaara, Veikko; Korhonen, Olli; Nygard, C. H.; Hakola, Tarja; Suvanto, S. (Scandinavian Journal of Work, Environment & Health, 1991)
Before and after a four-year follow-up, maximal oxygen consumption (VO2max) was determined for 67 municipal employees (initial age about 51 years). The VO2max (ml.kg-1) decreased 6% among the women and increased 8% among the men, the greatest and smallest change occurring for employees doing mental and physical work, respectively. The men's increase was associated with an increase in leisure-time physical activity. Work content was not associated with the level of VO2max for either gender. After the four years the women's absolute VO2max was about 66% of the men's. There were marked changes in VO2max at the individual level, the most marked decreases being associated with the use of medication in some cases. After the four years the women's VO2max of 63% was insufficient according to current recommendations. Therefore physically demanding jobs are not generally recommended for older women.